Characterization of ethyl acetate and n-butanol extracts of Cymbopogon schoenanthus and Helianthemum lippii and their effect on the smooth muscle of the rat distal colon. (24th April 2020) - Djemam, Nihed; Lassed, Somia; Gül, Fatih; Altun, Muhammed; Monteiro, Marisa; Menezes-Pinto, Daniela; Benayache, Samir; Benayache, Fadila; Zama, Djamila; Demirtas, Ibrahim; Morato, Manuela
Abstract: Ethnopharmacology relevance: Cymbopogon schoenanthus ( C. schoenanthus ) and Helianthemum lippii (H. lippii) are Saharan species found in the South West of Algeria, in the region of Bechar. Both plants are used in traditional medicine to treat gastrointestinal disorders. Objective: The aim of our study was to characterize the composition of the ethyl acetate (EtOAc) and n -Butanol ( n -BuOH) extracts of C. schoenanthus and H. lippii, and to elucidate and compare their effect on the reactivity of the rat distal colon. Main methods: The plants were macerated in a hydroalcoholic solution. After concentration, the aqueous solutions of the residues were submitted to liquid-liquid extractions to obtain EtOAc and n -BuOH extracts. The phenolic and flavonoid content of the extracts was determined by high performance liquid chromatography coupled with mass spectrometry with a time of flight analyzer (HPLC-TOF/MS). The effect of the extracts was tested on the rat distal colon, namely on the basal tone and on KCl- and Ach-induced precontracted preparations. Results: HPLC-TOF/MS identified 32 phenols and flavonoids in the extracts. The four extracts relaxed the rat distal colon, the effect being noticed on the basal tone and on the KCl- and Ach-induced precontractions. The EtOAc and the n -BuOH extracts of H. lippii decreased the basal tone of the rat distal colon more markedly than the correspondent extracts of C. schoenanthus . Moreover, the n -BuOH extract of C. schoenanthus decreased the basal tone more markedly than the EtOAc extract of this plant but there was no difference between extracts of H. lippii . The EtOAc extracts of both C. schoenanthus and H. lippii totally reverted both the KCl- and the Ach-induced precontraction of the rat distal colon. However, the n -BuOH extracts of the two plants reverted the Ach-precontracted colon but not the colon that has been precontracted with KCl. Conclusion: Extracts of H. lippii contain a higher level of phenols compared to the extracts of C. schoenanthus. All extracts of C. schoenanthus and H. lippii caused marked relaxation of the isolated rat distal colon, either when applied directly or when tested over KCl- and Ach-induced precontraction. These results give support to the use of C. shoenanthus and H. lippii in traditional medicine, namely for gastrointestinal diseases. Graphical abstract: Image 1